Changing Names with Style: Mutual Fund Name Changes and Their Effects on Fund Flows - COOPER, MICHAEL J.; GULEN, HUSEYIN; RAU, P. RAGHAVENDRA (Journal of Finance, 2005)
ABSTRACT We examine whether mutual funds change their names to take advantage of current hot investment styles, and what effects these name changes have on inflows to the funds, and to the funds' subsequent returns. We find that the year after a fund changes its name to reflect a current hot style, the fund experiences an average cumulative abnormal flow of 28%, with no improvement in performance. The increase in flows is similar across funds whose holdings match the style implied by their new name and those whose holdings do not, suggesting that investors are irrationally influenced by cosmetic effects.